UTILIZING 3D PRINTING TECHNOLOGY FOR ENHANCED PREOPERATIVE PLANNING IN ORTHOPEDIC SURGERY: A NARRATIVE REVIEW - Jha, Rakesh (Student’s Journal of Health Research Africa, 2024)
In orthopedic surgery, accuracy and careful preparation before surgery are essential for positive results. In this field, additive manufacturing, also called 3D printing technology, has become a game-changing instrument. It enables the creation of patient-specific anatomical models, custom surgical tools, and personalized implants, enhancing the accuracy and efficiency of surgical procedures. While the potential benefits are significant, the integration of 3D printing into routine practice and its long-term implications are still under exploration. This narrative review aims to systematically assess the current state of 3D printing technology in preoperative planning for orthopedic surgery, focusing on its applications, benefits, challenges, and the quality of the evidence supporting its use. The review highlights the diverse applications of 3D printing across various orthopedic procedures, including joint replacement, spine, and trauma surgeries. Studies indicate that 3D printing contributes to improved surgical planning, reduced operative times, and potentially better patient outcomes. However, challenges related to cost, accessibility, and the need for specialized training are noted. The review also discusses the quality of current research, emphasizing the need for more high-quality, long-term studies to better understand the technology’s impact. As 3D printing technology continues to advance, it holds the promise of further revolutionizing orthopedic surgery. Future research should focus on long-term patient outcomes, cost-effectiveness, and the development of guidelines for its use. The potential for 3D bioprinting and the creation of biological implants also opens new avenues for personalized and regenerative medicine. Clinicians and policymakers must weigh 3D printing’s revolutionary promise against its existing limitations. Research, training, and infrastructure are needed to maximize its benefits. As data increases, clinical standards and policies will be needed to standardize 3D printing in orthopedic preoperative planning for safety, efficacy, and equitable access.